Study of the Effect of Different Soil Conservation Measures in the Upland of Chotanagpur on Physico- Chemical Properties of Soil - S., Quraishi; S, Alam; A.K., Sinha (Journal of Soil and Water Conservation, 2022)
A study to evaluate the effects of the common type of terraces of the region (tati and graded terraces) on some important physico-chemical properties of soil as conducted at nine sites in the Ranchi District of Chotanagpur division. The results showed that on average, terraced lands had higher percentage of silt and clay and Organic Carbon as well as total and macro water stable aggregates, total pore space, water holding capacity and lesser value of dispersion ratio, erosion index than its unterraced counter part projecting that terraces have brought about considerable beneficial effects on the physico-chemical properties of the soil of the terraced land besides the enhanced ability of resistance to erosion and increased production capability. Both types of the terraces were however, found to be equally good for the region.